HAKIKAT DAN SISTEM NILAI DALAM KONTEKS PENDIDIKAN (Sistem Nilai: Keluarga, Masyarakat, Kebudayaan, dan Agama) - Muslimah, Muslimah (Jurnal Studi Agama dan Masyarakat, 2013)
Value on the philosophical view was considered as propitious. The measurements were ethics and morality. Islam has a different statement, that it viewed value as something or some cases as beneficence. There was value system in family, society, culture, and religion. Idealist community, realist community, and pragmatic community had a different opinion to determine the hierarchy of value. All of religions had a universal value. The value system in Islam, including Islamic education, was based on the normative category and law standard. All of them were based on al-Qurâan and Hadith..